The Requirements of Developing Countries' Health Systems Facing with COVID-19: A Case Study of Iran. (30th September 2020) - Ghanbarzadegan, A; Bastani, P; Emadi, F; Mohammadpour, M; Pourmohammadi, K; Javanmardi, S
Abstract: Background: Epidemic COVID-19 in 2020 was one of the crises that confronted the Islamic Republic of Iran's health system as a developing low-income country with many challenges. The purpose of this study is to explain the requirements of similar health systems in facing epidemics such as COVID-19 as well as sharing experiences of Iran. Methods: The present study was a qualitative study using content analysis of the Iranian Ministry of Health website (behdasht.gov.ir) during the official onset of COVID-19 in Iran (February 20) to March 7, 2020. To Integrate data, interviews with experts were used. In this regard, 4 national health policymakers and 5 provincial health managers were interviewed. After implementation using 8-step content analysis method, data were analyzed using MAXQDA software by research team members who had no conflict of interest. Results: The findings show that the disease began on February 20, 2020, with two cases of death from COVID-19 in Qom province in central Iran and within two weeks it has widely affected 31 provinces, with 4747 approved cases and 124 deaths. According to the results, the Islamic Republic of Iran's health system faced five major challenges to confronting with COVID-19: 1- Medical consumables supply 2- Hospital beds allocation and intensive care units (ICU) equipment 3-The lack of a comprehensive COVID-19 protocol in the country 4- the lack of a single command authority to deal with the crisis 5- Insufficient public health literacy and information as a result of social anxiety. Conclusions: Experiences of this case indicate that health systems require policy action to prevent and control diseases rather than other implementations. In this regard, training should be given to children and adolescents, at-risk persons and health system staff. In addition, to confront with COVID-19, an integrated policy implementation team should be established in collaboration with the health sector and other relevant bodies. Key messages: It seems obvious that policy implementation requires to prepare the country for future contingencies. A comprehensive National Prevention Protocol needs to be developed.